β-thymosins and interstitial lung disease: study of a scleroderma cohort with a one-year follow-up - De Santis, Maria (BioMed Central, 2011)
BACKGROUND: β-thymosins play roles in cytoskeleton rearrangement, angiogenesis, fibrosis and reparative process, thus suggesting a possible involvement in the pathogenesis of systemic sclerosis. The aim of the study was to investigate the presence of thymosins β(4), β(4 )sulfoxide, and β(10 )in bronchoalveolar lavage fluid of scleroderma patients with interstitial lung disease and the relation of these factors with pulmonary functional and radiological parameters. METHODS: β-thymosins concentrations were determined by Reverse Phase-High Performance Liquid Chromatography-Electrospray-Mass Spectrometry in the bronchoalveolar lavage fluid of 46 scleroderma patients with lung involvement and of 15 controls. RESULTS: Thymosin β(4, )β(4 )sulfoxide, and β(10 )were detectable in bronchoalveolar lavage fluid of patients and controls. Thymosin β(4 )levels were significantly higher in scleroderma patients than in controls. In addition, analyzing the progression of scleroderma lung disease at one-year follow-up, we have found that higher thymosin β(4 )levels seem to have a protective role against lung tissue damage. Thymosin β(4 )sulfoxide levels were higher in the smokers and in the scleroderma patients with alveolitis. CONCLUSIONS: We describe for the first time β-thymosins in bronchoalveolar lavage fluid and their possible involvement in the pathogenesis of scleroderma lung disease. Thymosin β(4 )seems to have a protective role against lung tissue damage, while its oxidation product mirrors an alveolar inflammatory status.